2019
DOI: 10.1108/stics-11-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Chinese civic education being globalised

Abstract: Purpose The purpose of this paper is to compare the curriculum developments of civic education in three emerging Chinese societies: China and two Special Administrative Regions of Hong Kong and Macao, which are increasingly under the impacts of globalisation in this information world. Design/methodology/approach The analytical method is used and the following are identified: active and global civic education-related learning units and key themes and main contents in official curriculum guidelines and updated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In addition to the inconsistency between curriculum documents and research related to GCE, there is empirical evidence from schools indicating an unexplored gap of GCE-related practices. Although Shi et al (2019) claim that it was less common for GCE-related goals and contents to be implemented with an immersion approach in schools in mainland China, meaning that GCE was not addressed as extensively in other formal subjects as it was in Hong Kong schools, secondary schools in mainland China rely heavily on outsourcing resources for the immersion approach (Hong 2019). This strategy of using outsourcing resources is shown through some activities implemented in parallel to the authorised subject of Moral Education in participating schools, fortified by various NGOs, foreign institutions and grassroots groups.…”
Section: The Case Of Chinese Secondary Schoolsmentioning
confidence: 99%
“…In addition to the inconsistency between curriculum documents and research related to GCE, there is empirical evidence from schools indicating an unexplored gap of GCE-related practices. Although Shi et al (2019) claim that it was less common for GCE-related goals and contents to be implemented with an immersion approach in schools in mainland China, meaning that GCE was not addressed as extensively in other formal subjects as it was in Hong Kong schools, secondary schools in mainland China rely heavily on outsourcing resources for the immersion approach (Hong 2019). This strategy of using outsourcing resources is shown through some activities implemented in parallel to the authorised subject of Moral Education in participating schools, fortified by various NGOs, foreign institutions and grassroots groups.…”
Section: The Case Of Chinese Secondary Schoolsmentioning
confidence: 99%
“…The public foundation course of college language in higher vocational colleges and universities integrates instrumentality and humanity and undertakes the important mission of cultivating morality and educating people [1][2]. In the development period of digital transformation of education, under the pattern of casting a firm sense of community in the Chinese nation, teachers of university language courses should play a good role in the main position of classroom teaching, scientifically and effectively carrying out the reform of course ideology and politics teaching to build an innovative course ideology and politics teaching paradigm, and fully excavate and integrate the course ideology and politics and the essence and essence of the Chinese outstanding traditional culture, so as to make it synergistic and compatible in the teaching of university language courses and to walk together in the same direction [3][4][5]. The creation of poetry in university language is not something that the general public can easily do.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, several researchers have shown a great deal of interest in observing curricula and programs initiated for citizenship competency (Reynolds, MacQueen, & Ferguson-Patrick, 2019;Shi, Chong, & Li, 2019;Göğebakan-Yildiz, 2018;Díaz, 2017; European Commission/EACEA/Eurydice, 2017; Larsen & Searle, 2017;Aktas, Pitts, Richards, & Silova, 2016). For example, a systematic textual analysis was intended to explore how global citizenship was mentioned in three primary school curriculum areas in Australia: English, mathematics, science, the arts, humanities and social sciences (HASS), English, and science.…”
Section: Introductionmentioning
confidence: 99%
“…Learning materials are varied in form; textbooks are one of them. Shi (2019) found that the dimensions of citizenship competency that are generally included in civic education textbooks for three emerging Chinese societies -China, Hongkong, and Macaoare knowledge of local cultural characteristics, global context, values, and attitudes needed to be a good citizen. However, citizenship is taught as a separate subject.…”
Section: Introductionmentioning
confidence: 99%